Penyebab-Penyebab Kesalahan Penggunaan Kata Bahasa Mandarin: Tinjauan Terhadap Mahasiswa Jurusan Bahasa Mandarin di Indonesia - Weifen, Qin (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
Chinese words’ usage errors in compositions of undergraduates are very attractive to be research, because the errors are truly has become the obstruction of communication in composition. The purpose of this study is to describe the cause factors of the Chinese words’ usage errors in compositions of undergraduates. Use the approach of International qualitative methodology and the data of this research is got from the students in Unesa and UWK. The data analysis contains the following procedures. First, identify the word usage errors and classify the types based on the linguistics taxonomy which consisting of phonology, semantics & lexical, morphological, and syntactic. Finally, it analyzes the cause factors from both the perspective of linguistics and non-linguistics. The study finding interference between Chinese and Indonesian is the main linguistics factor causing. At the same time, the strategy of communication and language environment of undergraduates are the non-linguistic factors causing. Moreover, if viewed from the students themselves, learning duration, exposure, language governance, and media of study are also affects the words’ usage in composition.